Kepemimpinan Ulama Dalam Tinjauan Sosiologi - Ali Murtadho (TAFAHUS: JURNAL PENGKAJIAN ISLAM, 2021)
Linking the theme of the study of leadership and ulama (clerics) from a sociological perspective is an interesting matter. Because, the theme of leadership and ulama (clerics) is a multidisciplinary field. On the other hand, ulama (clerics) have an important role in people's lives. Ulama (clerics) have a role in the context of rapid social, political, and economic change. Ulama—especially in Indonesia—is used to denote someone who has a deep knowledge of Islam and is a religious figure and occupies an important and strategic position in the social world. This article will discuss the Ulama (cleric) from the perspective of the sociology of leadership. The discussion in this article uses Max Weber's theory of charisma. As it is known, charisma is pinned on certain qualities of an individual's personality that are different from ordinary people, and he is treated as someone who has blessings from the supernatural, superhuman, or at least, specifically has extraordinary powers or qualities. Therefore, Max Weber's concept of charisma is used to analyze the charismatic scholars from Turkey and Indonesia. This charismatic cleric (ulama) is addressed to the figures of Badiuzzaman Said Nursi, Fethullah Gullen, KH. Hasyim Asy'ari, and KH. Ahmad Dahlan.